Exercise-induced changes of ventricular function in male and female amateur marathon runners as assessed by three-dimensional echocardiography. (14th October 2021) - Lasocka, Z.B; Dabrowska-Kugacka, A; Kaleta-Duss, A; Lewicka-Potocka, Z; Faran, A; Danilowicz-Szymanowicz, L; Nowak, R; Kaufmann, D; Raczak, G; Lewicka, E
Abstract: Introduction: The long-term endurance training is associated with an increased risk of both right (RV) and left ventricular (LV) dysfunction. However, males and females exhibit different cardiac adaptation to exercise. The aim of our study was to evaluate three-dimensional (3D) echocardiographic parameters of ventricular function before and after the marathon in male and female amateur athletes, and compare them between sexes. Methods: The study included 40 male (39±8 years) and 27 female (40±7 years) amateur athletes. Echocardiography was performed 2–3 weeks before (Stage 1) and immediately after (Stage 2) the marathon run. RV and LV area and function were assessed using standard and 3D echocardiography. Results: After the marathon, there was a significant increase in the RV size (indexed RV end-diastolic volume, 51.1±12.0 vs. 59.0±9.1 ml/m 2, p=0.003 in males; 48.8±11.0 vs. 60.0±11.1 ml/m 2, p<0.001 in females), with a decrease in the LV dimensions (indexed LV end-diastolic volume, 57.1±11.9 vs. 53.0±9.4 ml/m 2, p=0.026 in males; 66.2±7.9 vs. 60.1±9.5 ml/m 2, p=0.001 in females). RV systolic contractility, as assessed by ejection fraction (EF) and fractional area change (FAC), significantly decreased at Stage 2 in both studied groups, while post-race decrease in LVEF was observed only in males (p<0.05 for the interaction sex and stage). Conclusions: In both male and female amateur athletes, marathon running resulted in RV dilatation and reduction in function, with concomitant decrease in LV dimensions. However, 3D analysis revealed that strenuous exercise alters LV systolic function to a greater degree in men relative to women. Funding Acknowledgement: Type of funding sources: None.